2000
DOI: 10.1038/labinvest.3780042
|View full text |Cite
|
Sign up to set email alerts
|

Ethylnitrosourea Induces Neoplasia in Zebrafish (Danio rerio)

Abstract: SUMMARY:The zebrafish (Danio rerio) has been successfully used to discover hundreds of genes involved in development and organogenesis. To address the potential of zebrafish as a cancer model, it is important to determine the susceptibility of zebrafish to tumors. Germ line mutations are most commonly induced for zebrafish mutant screens by exposing adult male zebrafish to the alkylating agent, ethylnitrosourea (ENU). To determine whether ENU induces tumors, we compared the incidence of tumors in ENU-treated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 38 publications
1
65
0
2
Order By: Relevance
“…Water-soluble carcinogens can be added directly to the fish water and a number of chemical compounds that are carcinogenic in mammals induce tumor formation in zebrafish (Amatruda et al, 2002;Berghmans et al, 2005a;Goessling et al, 2007a, b). Exposure to dimethylbenzanthracene, ethylnitrosourea, N-methyl-N-nitro-Nnitrosoguanidine, diethylnitrosamine results in a variety of tumors in zebrafish or medaka (Oryzias latipes) (Okihiro and Hinton, 1999;Beckwith et al, 2000;Spitsbergen et al, 2000a, b;Mizgireuv et al, 2004;Lam and Gong, 2006;Mizgireuv and Revskoy, 2006). Most of the tumors that arise are hepatic but can also include other organs and tissues such as skin (papillomas), muscle (rhabdomyosarcomas and leiomyosarcomas), vasculature (hemangiosarcomas), testis (seminomas) and pancreas (pancreatic carcinomas) (Okihiro and Hinton, 1999;Beckwith et al, 2000;Spitsbergen et al, 2000a, b;Mizgireuv et al, 2004;Lam and Gong, 2006;Mizgireuv and Revskoy, 2006).…”
Section: Chemical Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Water-soluble carcinogens can be added directly to the fish water and a number of chemical compounds that are carcinogenic in mammals induce tumor formation in zebrafish (Amatruda et al, 2002;Berghmans et al, 2005a;Goessling et al, 2007a, b). Exposure to dimethylbenzanthracene, ethylnitrosourea, N-methyl-N-nitro-Nnitrosoguanidine, diethylnitrosamine results in a variety of tumors in zebrafish or medaka (Oryzias latipes) (Okihiro and Hinton, 1999;Beckwith et al, 2000;Spitsbergen et al, 2000a, b;Mizgireuv et al, 2004;Lam and Gong, 2006;Mizgireuv and Revskoy, 2006). Most of the tumors that arise are hepatic but can also include other organs and tissues such as skin (papillomas), muscle (rhabdomyosarcomas and leiomyosarcomas), vasculature (hemangiosarcomas), testis (seminomas) and pancreas (pancreatic carcinomas) (Okihiro and Hinton, 1999;Beckwith et al, 2000;Spitsbergen et al, 2000a, b;Mizgireuv et al, 2004;Lam and Gong, 2006;Mizgireuv and Revskoy, 2006).…”
Section: Chemical Mutagenesismentioning
confidence: 99%
“…Exposure to dimethylbenzanthracene, ethylnitrosourea, N-methyl-N-nitro-Nnitrosoguanidine, diethylnitrosamine results in a variety of tumors in zebrafish or medaka (Oryzias latipes) (Okihiro and Hinton, 1999;Beckwith et al, 2000;Spitsbergen et al, 2000a, b;Mizgireuv et al, 2004;Lam and Gong, 2006;Mizgireuv and Revskoy, 2006). Most of the tumors that arise are hepatic but can also include other organs and tissues such as skin (papillomas), muscle (rhabdomyosarcomas and leiomyosarcomas), vasculature (hemangiosarcomas), testis (seminomas) and pancreas (pancreatic carcinomas) (Okihiro and Hinton, 1999;Beckwith et al, 2000;Spitsbergen et al, 2000a, b;Mizgireuv et al, 2004;Lam and Gong, 2006;Mizgireuv and Revskoy, 2006). The basic histological and molecular characteristics of chemically induced neoplasia in zebrafish show significant similarity to human cancer including increased cell proliferation, atypical nuclear morphology and low degree of cell differentiation.…”
Section: Chemical Mutagenesismentioning
confidence: 99%
“…Tens to hundreds of milligrams of skeletal muscle may be isolated from a single fish, providing an ample supply of tissue for study. The pathologies zebrafish incur, such as various tumors, are morphologically similar to those found in mammals (Beckwith et al, 2000), yet the costs for such analyses are much less due to the smaller size of zebrafish.…”
Section: The Origins Of Zebrafish As a Gerontological Modelmentioning
confidence: 99%
“…Post-mitotic tissues, including skeletal muscle, brain, heart, and eye may thus be easily harvested for study. Replicating tissues may also be obtained, and zebrafish develop a wide variety of neoplasms with morphological similarity to mammalian tumors (Beckwith et al, 2000). Pathological analysis is also more cost-effective in zebrafish due to the ability to place an entire adult fish on a single microscope slide.…”
Section: Zebrafish Versus Lab Mice-50 Times Smaller Yet Live 50% Longermentioning
confidence: 99%
“…Not surprisingly, the alkylating mutagen N-ethyl-N-nitrosourea, which introduces point mutations and is commonly used in forward and reverse genetic screens, has also been found to induce cancer. Following a group of animals from a mutagenesis screen, Beckwith et al (15) found that all fish developed skin papillomas over time, but not invasive skin cancers.…”
Section: Treatment With Mutagensmentioning
confidence: 99%